Circulation, transport and dispersion of hydrocarbon plumes in the North Brazilian equatorial broadband - VARONA GONZÁLEZ, Humberto Lázaro (2018)
This Ph. D. thesis focuses on a study of hydrodynamics and oil/gas blowouts in deep water using the Regional Ocean Model System (ROMS) and GAS_DOCEAN models. The first objective was to analyze the potential impact of the Amazon and Pará Rivers on salinity, temperature and hydrodynamics in the Western Tropical North Atlantic between 60.5º-24ºW and 5ºS -16ºN. The ROMS was used to simulate the ocean hydrodynamics with 0.25º horizontal resolution and 32 vertical levels. In the ROMS model two experiments are carried out, one taking into account the discharge of freshwater from the rivers and the second, without releasing freshwater into the Atlantic ocean. The results of both simulations are compared determining the changes in temperature, salinity and surface currents produced by the influence of the rivers discharge. The Sea Surface Temperature difference between the simulations with river and no-river was about 2ºC. The Sea Surface Salinity difference was about 8 psu in the plume area confined to the littoral, with maximum from August to December and 4 psu in the area of the North Equatorial Countercurrent (NECC). The surface current velocities are stronger in the experiment with river and the strongest, close to the coast. The experiment with river causes a phase shift in the zonal currents anticipating the strongest velocities in the second semester of the year in 2 months, changing the seasonal cycle. The Mixed Layer Depth and Isothermal Layer Depth (ILD) in the experiment with river is 20 - 50 m shallower over the entire extension of the Amazon plume. The freshwater river discharge perform a fundamental role in the formation of Barrier Layer. The Oceanic Heat Content in the river experiments is smaller than the experiment without rivers, principally as a result of the shifts of the ILD. The second objective focuses on analyzing the behavior of oil/gas plumes from blowouts into deepwater. The simulations with the GAS_DOCEAN model were carried out in three points located at 50ºW, 5.25ºN, 44.5ºW, 0.5ºN and 42.75ºW, 1ºS . The time step was adjusted due to the particular oceanographic conditions at each point, in which, the initial velocity tends to zero and the coefficient 0.1 of the original equation was replaced by 0.0250 and 0.0375. All the plumes behaved as type 3. The seasonal current speed was small from the bottom to the surface, usually not exceeding 0.25 ms⁻¹; the maximum displacement of the plumes from its point of origin was not greater than 1 m. The mean plumes diameter on the surface varied between 54 and 79.7 m and the arrival time to the surface was from 7.25 to 8.05 hours.